Law enforcement, illegal activity and elephant status in Mago and Omo National Parks and adjacent areas, Ethiopia - Yirmed Demeke (Pachyderm)
A July to December 2002 projectfocused on monitoring the strength of law enforcement effort and the extent of illegal activity vis a vis wildlife also attempted to collect data on status of elephant populations on Omo and Mago NP's in southwest Ethiopia. The estimated elephant population in Mago NP is 200 animals: during the study elephant were observed 12 times in this area with one of those times being an observation of 167 animals. This estimation is 33% lower than the 1997/98 estimate, and it is considered that probably 48% of the Park may be occupied by elephant. Omo NP does not seem to have any permanent elephant populations, during the study elephant were only seen 3 times and one of these sightings involved a group of 327 animals. Due to budgetary constraints patrol staff is insufficent, and when arrests are made the penal system is very lax when dealing wildlife offenders. The authors full report is also in file. (Demeke, 2003)